2019
DOI: 10.1007/s00167-019-05389-3
|View full text |Cite|
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction with concomitant meniscal surgery: a systematic review and meta-analysis of outcomes

Abstract: Purpose The aim of this review was to compare the clinical outcomes of anterior cruciate ligament reconstruction (ACLR) with either meniscal repair or meniscectomy for concomitant meniscal injury. The primary hypothesis was that short-term clinical outcomes (≤ 2-year follow-up) for ACLR concomitant with either meniscal repair or resection would be similar. The secondary hypothesis was that ACLR with meniscal repair would result in better longer term outcomes compared with meniscal resection. Methods The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 66 publications
5
64
1
1
Order By: Relevance
“… 33 Moreover, a recent meta-analysis emphasized the role of the meniscus in knee stability, reporting that ACLR with concomitant meniscal repair reduced anterior knee joint laxity compared with ACLR with meniscectomy. 46 …”
Section: Discussionmentioning
confidence: 99%
“… 33 Moreover, a recent meta-analysis emphasized the role of the meniscus in knee stability, reporting that ACLR with concomitant meniscal repair reduced anterior knee joint laxity compared with ACLR with meniscectomy. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Despite dissimilar clinical outcomes, both meniscal repair and meniscectomy are acceptable treatments for concomitant meniscal injuries in patients with a chronic ACL injury. 5,26,35,38 Cohen et al 5 reported an increased incidence of arthrosis and poor function at long-term follow-up (10-15 years) after ACLR with meniscectomy. Singh et al 38 revealed that ACL deficiency with concomitant meniscal injuries was not related to poor outcomes at short-term follow-up (3.5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Almost fifteen percent of the global population over 60 years suffers from PTOA 3 and whose further development will lead to disability. Anterior cruciate ligament meniscal surgery may restore joint function but does not affect PTOA pathogenesis 4 . Current treatments are restricted to behavioral interventions and ultimately joint replacement surgery.…”
Section: Introductionmentioning
confidence: 99%